2010
DOI: 10.1158/0008-5472.can-09-3362
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of DNA-Dependent Protein Kinase Leads to Spindle Disruption and Mitotic Catastrophe with Attenuated Checkpoint Protein 2 Phosphorylation in Response to DNA Damage

Abstract: DNA-dependent protein kinase catalytic subunit (DNA-PKcs) is well known as a critical component involving the nonhomologous end joining pathway of DNA double-strand breaks repair. Here, we showed another important role of DNA-PKcs in stabilizing spindle formation and preventing mitotic catastrophe in response to DNA damage. Inactivation of DNA-PKcs by small interfering RNA or specific inhibitor NU7026 resulted in an increased outcome of polyploidy after 2-Gy or 4-Gy irradiation. Simultaneously, a high incidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 43 publications
6
97
0
2
Order By: Relevance
“…Furthermore, Shang et al (30) recently reported that inactivation of DNA-PKcs resulted in spindle disruption and centrosome instability.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Shang et al (30) recently reported that inactivation of DNA-PKcs resulted in spindle disruption and centrosome instability.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of apoptosis and centrosome amplification caused by SF-1 deficiency may explain why Sf-1-null adrenogenital primordial cells die, as centrosome amplification causes aberrant mitosis and subsequent cell cycle arrest or cell death. 13,21 It would be interesting to examine whether the adrenogenital primordial cells of these Sf-1-null mice contain multiple centrosomes before they die. This experiment will not be easy because one has to catch the short time window at around E11.5 when these progenitor cells are dying.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of DNA-PK increases polyploidy and mitotic catastrophe after irradiation and attenuates Chk2 phosphorylation in an ATM-independent manner (Shang et al, 2010). Despite the ability of DNA-PK inhibitors to potentiate chemo-and radiotherapy in vitro and in vivo, the underlying factors that regulate the contribution of cell cycle arrest and cell death to the overall loss of clonogenicity remain unclear.…”
Section: Arrest/senescencementioning
confidence: 99%